ANALISIS FAKTOR-FAKTOR SOSIAL YANG MEMPENGARUHI KEBERHASILAN KELOMPOK TANI HORTIKULTURA DI KELOMPOK WANITA TANI LEGOWO DUSUN KEMRANGGEN KABUPATEN WONOSOBO - Machmudah, Luthfiana; Satmoko, Sriroso; Mardiningsih, Dyah (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol.13, No.2, 2019, 2019)
Farmer groups have an important role in the progress of agricultural development. Many factors influence progressively by farmer groups. These factors are motivation andspirit to work in a group, agricultural extension agent, coaching by village officials and group norms. The progress of farmer groups could be seen from the learning class values, cooperation's mode, production units and business units. The main purpose of this research is to analyze social factors (motivation and spirit to work in a group, agricultultural extension agent, coaching by village officials and group norms), to analyze the progress of groups and to analyze influence of social factors to the progress of groups. Research already implemented in November-December 2018. The research method was a survey. The research sample was a member of the Legowo Women's Farmer Group Wulungsari, Wonosobo Regency. Sampling used by purposive sampling method, as many as 39 respondents. The analyis used by descriptive analysis and multiple regression analysis. The results of research indicated that the level of work motivation of the Legowo Women's Farmer Group was classified as high (90%), the role of agricultural extension agent was high (63,33%), the coaching by village officials was mostly high (56,67%) and group norms was high (100%). The level of high progress learning unit is classified as medium (83,33%), the group's progress as cooperation's mode classified as medium (83,33%), the group's  progress as a production unit is high (96,67%) and the progress group as a business unit classified as medium (93,33%)